Thermoelectric properties of p-type CoSb3 nanocomposites with dispersed CoSb3 nanoparticles - Yang, L. (2014)
CoSb3 nanocomposites with different contents of CoSb3 nanoparticles were prepared by mixing nanosized CoSb3 particles obtained via polyol method and micron-sized particles obtained via solid state reaction. X-ray diffractometer and field emission scanning electron microscope were used to characterize the prepared products. The thermoelectric properties of the nanocomposites with different amounts of nanoparticles as dispersants were measured from room temperature to around 500 °C. Due to the grain boundaries scattering, the lattice thermal conductivity was observed to decrease as the amount of nanoparticles increased. The electrical properties were also improved by the addition of nanoparticles. The ZT value of the nanocomposites with 10 wt % of nanoparticles was nearly doubled that of the sample without any nanoparticles.